Analisis Perlindungan Hukum Pada Perusahaan Fintech P2P Lending Dengan Jaminan Fidusia (Studi Kasus PT Modal Rakyat Indonesia) - Natasya Mauly N, Denayu; Rasji, Rasji (LPPM Universitas Ekasakti Padang, 2024)
This study examines legal protections in Fintech peer-to-peer (P2P) lending companies utilizing fiduciary guarantees, with a specific focus on the case of PT Modal Rakyat Indonesia. It contextualizes the necessity of guarantee mechanisms in financial transactions and underscores the critical need for legal protections for both creditors and debtors within the Fintech P2P framework. The research methodology involves a legal analysis of the Fiduciary Guarantee Law and a detailed case study of PT Modal Rakyat Indonesia. The findings underscore the significance of creditor preference rights and the processes for dispute resolution following a default, discussing their broader implications for Fintech P2P lending practices.